Morton Satin: Death in the Pot: the Impact of Food Poisoning on History - Clark, Letitia (Petits Propos Culinaires, 2013)
Morton Satin: Death in the Pot: the Impact of Food Poisoning on History: Prometheus Books, 2007, 258 pp., hardback, £24.95.